Evaluation of Implementation Green Construction of Garut City Plaza Mall Project - Sukmalaras, Ratu Mafas; Soekiman, Anton; Sugiri, Tia; Kusmana, Dody; Pratiwi, Andini Radisya (Universitas Islam Sultan Agung, 2024)
Construction projects in Indonesia are rising, but many adversely affect the environment. Green Construction presents a solution to mitigate these impacts, aiming to harmonize environmental sustainability with present and future human needs. Evaluating the implementation of Green Construction in projects is crucial. This study employed the 2015 Green Construction Assessment Model by W.I. Ervianto to assess Green Construction achievements and conducted interviews to identify implementation obstacles in the City Plaza Garut Mall Building Development project. The research revealed that the Green Construction achievement score in the Garut City Plaza Mall Building project was 16.15 out of 21.92, equivalent to 74% of its potential. Although this is the highest Green Construction score achieved in Indonesia, opportunities for improvement persist. Several aspects require optimization. This study underscores the necessity of enhancing Green Construction implementation in construction projects to attain a sustainable balance between environmental conservation and human necessities.